DOI: 10.31979/etd.xe32-quws
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Intracellular Concentrations of Flavonoids in MDA-MB-231 Cells Using HPLC-Coupled Mass Spectrometry

Abstract: Flavonoids are polyphenolic compounds widely distributed in fruits, vegetables and beverages. In recent years, flavonoids have been found to be beneficial to human health due to their anti‐oxidant and anti‐tumor activities. Our lab has investigated the ability of flavonoids to induce cytotoxicity in human breast cancer cell lines. We have discovered that some compounds can induce cytotoxicity very readily whereas others are not. We hypothesize that this difference is attributed to the compounds ability to tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
(55 reference statements)
0
1
0
1
Order By: Relevance
“…In addition, several studies have indicated high cytotoxic and anticancer activity of flavonoids [15,16]. Studies have shown that flavonoids may reduce breast cancer cell proliferation [17,18] and human colon carcinoma cell proliferation [19]. Flavonoid anticancer activities include inhibition of cell growth, inhibition of protein kinase activities, induction of apoptosis [20].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, several studies have indicated high cytotoxic and anticancer activity of flavonoids [15,16]. Studies have shown that flavonoids may reduce breast cancer cell proliferation [17,18] and human colon carcinoma cell proliferation [19]. Flavonoid anticancer activities include inhibition of cell growth, inhibition of protein kinase activities, induction of apoptosis [20].…”
Section: Resultsmentioning
confidence: 99%
“…Por isso, elas podem ser mais expostas aos metabólitos de flavanonas no meio de cultura. Já in vivo, a quantidade dos metabólitos expostos às células pode não ser tão alta quanto in vitro, devido à superfície de crescimento limitada no ambiente celular (Pham, 2012).…”
Section: Peróxido De Hidrogêniounclassified